Pengembangan Media Pembelajaran Hikayat Hang Tuah Berbasis 3D Hologram Untuk Kelas X SMA - Adlina, Adlina; Dermawan, Taufik; Karkono, Karkono (UNIB Press, 2024)
The limitations of Hikayat learning media made researchers take the initiative to develop 3D hologram-based learning multimedia. This development research is used as a form of actualization and utilization of technology in learning Hikayat in high school. This research adapts the Research and Development (R&D) research design using the ADDIE method (Analysis, Design, Development, Implementation and Evaluation). Researchers took 30 samples from the total population for data processing. In relation to data sources and data collection techniques, researchers used three data collection techniques, namely observation, interviews, and questionnaires. The observation technique is used to explore data about the way teachers teach, the media that teachers usually use in the process of learning Hikayat, and the enthusiasm of students in learning Hikayat in class X Science 2, X Science 5, and X Science 6 at SMA Negeri 2 Jember. The development of multimedia prototypes based on holography technology uses the Hang Tuang Hikayat as material that is adapted to the context and development of students. The focus of the problems in this study are (1) the needs of teachers and students regarding the learning media for Hikayat texts (2) the design of learning media using 3D Holograms (3) The use of media for learning Hikayat in high school. The purpose of this research is to produce HOLY (Hologram Literary) products. The product results in the form of a video about the Hikayat story by modifying the 3D model and adding audio. The product results are displayed by utilizing a 3D hologram fan projector. HOLY multimedia combines text, images, and digital animation that will develop creativity and imagination so that it can process students' thoughts, feelings and attention in learning.